2022
DOI: 10.3390/insects13070571
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MRJP3 and HSP70 mRNA Levels in Apis mellifera L. Workers after Dietary Supplementation with Proteins, Prebiotics, and Probiotics

Abstract: Royal jelly is an essential substance for the development of bees from larval to adult stages. Studies have identified a group of key proteins in royal jelly, denominated major royal jelly proteins (MRJPs). The group currently consists of nine proteins (MRJP1–MRJP9), with MRJP1 being the most abundant and MRJP3 being used as a microsatellite marker for the selection of queens with a greater production of royal jelly. The diet of bees is mostly composed of proteins, and supplementing this intake to encourage a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the past few decades, several studies have shown that HSPs play important roles in various viral infections. For example, latent infection of herpes simplex virus-2 (HSV-2) increased the HSPs in human neuroblastoma cells, HSP70 mRNA levels increased in mouse L cells after HSV-1 and HSV-2 infection, and the expression level of HSP70 and HSP90 were increased in human B lymphocytes infected with EB virus ( 13 15 ). In addition, HSP70 is associated with the capsid precursor P1 of poliovirus type 1 and coxsackievirus B1 ( 16 ), the expression levels of HSP70 and HSP40 in lymphocytes of HIV-1 infected patients increased as well ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, several studies have shown that HSPs play important roles in various viral infections. For example, latent infection of herpes simplex virus-2 (HSV-2) increased the HSPs in human neuroblastoma cells, HSP70 mRNA levels increased in mouse L cells after HSV-1 and HSV-2 infection, and the expression level of HSP70 and HSP90 were increased in human B lymphocytes infected with EB virus ( 13 15 ). In addition, HSP70 is associated with the capsid precursor P1 of poliovirus type 1 and coxsackievirus B1 ( 16 ), the expression levels of HSP70 and HSP40 in lymphocytes of HIV-1 infected patients increased as well ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is further proven from mrjp1 also not regulating at either day 5 or day 9 and Hsp70 having no regulation at day 9. As royal jelly is important for development and Hsp70 would show abundant changes when bees would experience unusual situations of stress (Oliveira et al, 2022), such as being put inside a cage to live with no room to fly properly, which is in itself a type of stress. Hydrogen peroxide, which works by producing destructive hydroxyl free radicals that can attack membrane lipids, DNA, and other essential cell components (Brudzynski, 2020), was avoided by bees (Figure 2A) and led to significant early toxicity when administered at 4,000 ppb (Figure 1).…”
Section: B Amentioning
confidence: 99%